Development of ICT-Based Learning Media as an Extension Tool for the Production of Liquid Organic Fertilizer - Hidayat, Rohmat; Maulida, Pusparani; Nasirudin, Mohamad (Program Studi Agribisnis, 2024)
This research aims to develop an agricultural learning media called Em Penyu (Media Penyuluhan Pertanian). It is an extension tool based on Information Communication and Technology (ICT) as an alternative solution in supporting agricultural extension activities dealing with liquid organic fertilizer. This study used the Research and Development method based on the ADDIE development model. The subjects of this research were 25% of the members of the Ngaren Farmers Group. The data collection techniques are interviews and questionnaires. Researchers designed agricultural extension media in the form of videos. The results of this study indicate that (1) the assessment of the validity of the media by material experts gets a percentage of 71.875% in the good category, and the assessment by media experts gets a percentage of 85.294% in the very good category. (2) Assessment of farmers' response to the media gets a percentage of 84.5% in the very good category. Based on these results, it can be interpreted that Em Penyu is suitable for use in agricultural extension activities and farmers have given a positive response regarding the development of this agricultural extension media. So it is hoped that it can also be a supporter in advancing the agricultural sector.